Interpretasi Sebaran Batuan Andesit di Desa Karangcegak Kecamatan Kutasari Kabupaten Purbalingga Berdasarkan Data Resistivitas dengan Konfigurasi Wenner-Schlumberger - Sehah, Sehah (Fakultas Teknik Geologi Universitas Padjadjaran, 2022)
Karangcegak Village, Kutasari District, Purbalingga Regency has high andesite rock potential. Andesite rock has been mined traditionally by the local community, but its utilization is still not optimal. This study aims to determine the distribution of andesite rocks based on the resistivity data of the Wenner-Schlumberger configuration. Resistivity data acquisition was done on four trajectories with a length of 195 m. The GL-01 trajectory is located at a geographical position of 07°19'23.3” S; 109°17'19.6” E, the GL-02 trajectory is located at position of 07°19'23.9” S; 109°17'21.1” E, the GL-03 trajectory is located at position of 07°19'24.3” S; 109°17'21.8” E, and the GL-04 trajectory is located at position of 07°19'25.1” S; 109°17'22.8” E. Calculation of field data (i.e. voltage and current) were carried out to obtain apparent resistivity data. The calculated data are stored in the notepad format, and are used as input data for resistivity data modeling. The resistivity data modeling were carried out in 2D and 3D using RES2DINV 3.54 and VOXLER 4.0. The structure of the subsurface rock layers obtained on the four trajectories consists of three types of rock, i.e. the lava breccia with a resistivity value of less than 1,510 m, weathered andesite rock with resistivity values ranging from 1.511 – 4,000 m, and andesite rock with resistivity values are more than 4,000 m. Andesite rocks are found in all trajectories with a depth of 0 – 36 m. Based on the results of the analysis of the 2D resistivity cross section in each trajectory and the 3D pseudo-resistivity, the potential of andesite rock in the study area is estimated to be very large. The study results also show that the direction of the distribution of andesite rocks is in accordance with the direction of the lava flow of Slamet Volcano, i.e. from southwest to southeast.